The Optimization Design of an Ionic Liquid Composite Material for Nitrogen Removal - Liu Bao-you; Wang Tao (MATEC Web of Conferences, 2017)
A kind of EMIMTA ionic liquid was prepared. The viscosity and the absorption amount of NO2 of EMIMTA-TEA composites were measured in different proportion and different temperature. Origin software was used to fit the mathematical equation of the relationship between the viscosity, the absorption amount of NO2 and the mole fraction of the ionic liquid. By the lingo software, the better proportion of Ionic liquid and triethanolamine is optimized. The results show that both the viscosity and the absorption amount of NO2 decrease with the increase of the mole fraction of EMIMTA, which are in accordance with the two order polynomial equation. In order to obtain better absorption amount of NO2 and lower viscosity of composites, taking the absorption amount of NO2 / viscosity maximization as the optimization goal, the viscosity and absorption amount equation NO2 as constraint conditions, the mathematical model of nonlinear programming is established and solved. The results show that when the molar ratio of the ionic liquid is 0.4091, the viscosity of the composite is 47.5 mPa / s, and the absorption amount of NO2 is 0.7744 g . g-1. This paper has some guiding significance for the optimization design of ionic liquid composites.